2008
DOI: 10.1111/j.1541-4337.2007.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

The Carotenoid Pigment Zeaxanthin—A Review

Abstract: Scientific evidence linking several diseases with diet has brought to light the beneficial effects of a number of natural food ingredients. Zeaxanthin is one such natural pigment emphasized for its critical role in the prevention of age-related macular degeneration (AMD), the leading cause of blindness. The review highlights zeaxanthin as a carotenoid pigment with promising nutraceutical implications, and enumerates the important plant and microbial sources for its production, the absorptive pathway of zeaxant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
139
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(155 citation statements)
references
References 172 publications
0
139
1
5
Order By: Relevance
“…They may also be esterified with fatty acids or complexed with sugars and proteins [17]. The conjugate double-bond structure found in carotenoids also determines biological functions, such as absorption of light during photosynthesis, energy transfer, and protection from harmful effects of light on the cells during the photosynthesis.…”
Section: Carotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also be esterified with fatty acids or complexed with sugars and proteins [17]. The conjugate double-bond structure found in carotenoids also determines biological functions, such as absorption of light during photosynthesis, energy transfer, and protection from harmful effects of light on the cells during the photosynthesis.…”
Section: Carotenoidsmentioning
confidence: 99%
“…The next step, α-carotene, β-carotene, and γ-carotene are produced from lycopene via ring formation in the end groups by lycopene cyclase. α-and β-carotenes are the xanthophylls as a result of hydroxylation by β-carotene hydroxylase (Figure 2) [16,17]. …”
Section: Biosynthesis Of Terpenes and Carotenoidsmentioning
confidence: 99%
“…In vitro studies, it has been suggested that carotenoids ( -cryptoxanthin, lycopene) stimulated bone formation and mineralization, and may prevent osteoporosis development (Yamaguchi & Uchiyama, 2004). Zeaxanthin and lutein might possess the function of preventing age-related macular degeneration (Sajilata et al, 2008). Epidemiological evidence has indicated that lycopene may protect individuals from colorectal cancer and men from prostate cancer .…”
Section: Carotenoidsmentioning
confidence: 99%
“…Spolu so zeaxantínom má kľúčovú úlohu v prevencii vekom podmienenej makulárnej degenerácie, ktorá vedie k strate zraku v strede zorného poľa v dôsledku poškodenia očnej sietnice. Takisto znižuje riziko sivého zákalu (katarakty), ktorý je hlavnou príčinou zhoršeného zraku v rozvinutých krajinách (Sajilata et al, 2008;Šivel et al, 2013).…”
unclassified